Hubungan Asupan Zat Gizi Makro dengan Status Gizi Berdasarkan LILA pada Remaja Putri di SMA Negeri 2 dan 4 Kecamatan Tuban - Indi Antika Falentina; Eva Silviana Rahmawati; Lilia Faridatul Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Problem: Chronic energy deficiency is a condition in which a person experiences a long-lasting and chronic lack of energy and protein. This condition can be determined through the measurement of MUAC (Upper Arm Circumference) as one of the indicators of nutritional status measurement. with a threshold of 23.5 cm. Objective: This study is to determine the relationship between macronutrient intake, iron and physical activity with nutritional status based on MUAC in SMA Negeri 2 and 4 Tuban District. Method : Analytical research method with a cross sectional approach. The sample of adolescents in SMA Negeri 2 and 4 Tuban Sub-district amounted to 237 respondents, determined by cluster random sampling technique. Analysis of the study using spearman correlation statistical test. Result: showed that adolescent girls with weight deficit energy intake had Chronic energy deficiency nutritional status with a percentage (93.5%), protein (76.5%), fat (76.6%), carbohydrates (86.2%). The results of statistical tests found a significant relationship between macronutrient intake and Chronic energy deficiency (p-value = 0.000). Conclusion: of this study is that macronutrients can affect the incidence of Chronic energy deficiency in adolescents. The lower the intake of macronutrients, the more adolescent girls are at risk of chronic energy deficiency